Life cycle exposure to propiconazole reduces fecundity by disrupting the steroidogenic pathway and altering DNA methylation in zebrafish (Danio rerio). (February 2020) - Teng, Miaomiao; Chen, Xiangguang; Wang, Chen; Song, Min; Zhang, Jie; Bi, Sheng; Wang, Chengju
Highlights: Life cycle toxic assessment of propiconazole was examined in zebrafish. Propiconazole caused growth inhibition and reduced the fecundity of F0. The expression of genes in HPGL axis were disrupted in zebrafish by propiconazole. Propiconazole inhibited F1 embryonic development via altering DNA methylation of F0. Abstract: Propiconazole is fungicide widely used in agriculture, which may enter aquatic ecosystems and affect organisms. In this study, zebrafish ( Danio rerio ) were exposed to environmentally relevant levels of propiconazole throughout the life cycle, from embryo to sexually mature adults, and the effects on growth, reproduction, and offspring viability were investigated. To investigate the mechanisms of propiconazole action, the sex steroid hormones and the expression of genes related to the hypothalamus-pituitary-gonad-liver (HPGL) axis and DNA methylation were examined. Growth decreased in the parental zebrafish (F0) after exposure to propiconazole for 120 days. In males, increases in the levels of 17β-estradiol and vitellogenin were observed. The alterations in sex steroid hormones were regulated by the expression of genes involved with the HPGL axis. The decreases in fecundity and fertilization of the F0 was induced by the global DNA methylation, and then may result in the abnormal development of the F1. Therefore, propiconazole disrupted the steroidogenic pathway and caused changes in global DNA methylation that induced reproductive toxicity.